Community Participation in the Development of Krajan Cultural Market as Local Wisdom-Based Tourism - Adi Nur Setiawan; Yosafat Hermawan Trinugraha; Dwi Astutik (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
Abstract This study aims to analyze community participation related to the development of the Krajan Cultural Market, as a tourism based on local wisdom. This participation includes the community in Manyarejo Village, Plupuh District, Sragen Regency. The method that researchers use in this study is a qualitative method. The results of this study include the potential of ancient fossils, regional arts as local wisdom including the Buto Balung dance, the Rempeg Balung Buto dance, the art of stringed music made of bamboo, and the klotekan with the name gejog lesung. This study discusses forms of community participation to take advantage of existing potential through the Krajan Cultural Market, using Jim Ife's thoughts on Participation, Jim Ife's Participation through a participatory democracy approach, this approach has four characteristics including decentralization, accountability, education, and obligations. The parties that play a role in the development of the Krajan Cultural Market are the managers as the main stakeholders, the Manyarejo Village government, artists, traders, cultural administrators, and tourists. Keywords: participation, Tourism, and Local wisdom Abstrak Penelitian ini memiliki tujuan untuk menganalisis tentang partisipasi masyarakat yang berkaitan dengan pengembangan Pasar Budaya Krajan, sebagai sebuah pariwisata yang berbasis kearifan lokal yang dimiliki. Partisipasi tersebut meliputi masyarakat yang ada di Desa Manyarejo, Kecamatan Plupuh, Kabupaten Sragen. Metode yang peneliti gunakan dalam penelitian ini ialah metode kualitatif. Hasil dari penelitian ini meliputi potensi fosil purbakala, kesenian daerah sebagai kearifan lokal diantaranya tari Balung Buto, tari Rempeg Balung Buto, kesenian musik gambus yang terbuat dari bambu, dan klotekan dengan nama gejog lesung. Penelitian ini membahas terkait bentuk partisipasi masyarakat untuk memanfaatkan potensi yang ada melalui Pasar Budaya Krajan, menggunakan pemikiran Jim Ife mengenai Partisipasi, Partisipasi Jim Ife melalui pendekatan demokrasi partisipatif, pendekatan ini memiliki empat karakteristik diantaranya desentralisasi, akuntabilitas, pendidikan, dan kewajiban. Pihak-pihak yang berperan dalam pengembangan Pasar Budaya Krajan ialah pengelola sebagai stakholder utama, pemerintah Desa Manyarejo, Pelaku kesenian, pedagang, pamong budaya, maupun para wisatawan. Kata Kunci: Partisipasi, Pariwisata, dan Kearifan Lokal